Size matters: larger fragments of riparian forest in urban areas support functional diversity of soil bacteria more than smaller ones - Koster, Gabriela; Jaźwa, Małgorzata; Przemieniecki, Sebastian Wojciech; Musielok, Łukasz; Azarbad, Hamed; Klimek, Beata (Frontiers in Microbiology, 2025)
Soil microorganisms are relatively poorly studied in urban ecosystems, particularly within unmanaged woodlands that form island-like patches of vegetation. We surveyed soil bacteria on Salix spp. dominated riparian-like forest patches in Kraków, the second largest city in Poland, to find out which environmental factors influence their activities and functional diversity, measured using Biolog® ECO plates. Our results showed that soil bacterial alpha functional diversity, including substrate richness (number of substrates decomposed) and Shannon diversity, were positively correlated with patch area and number of vascular plant species in the forest floor vegetation layer. However, soil bacterial beta functional diversity (substrate use pattern, CLPP – community level physiological profiles) was primarily driven by patch area and soil physicochemical properties. Our results suggest that the positive effect of patch area (biogeographic effect) on soil bacterial functional diversity may be primarily through stabilisation of environmental conditions, as the amplitude of environmental fluctuations is reduced on larger plots compared to smaller ones. Taken together, our study provides important insights into the relationship between patch area, soil properties, vegetation characteristics, soil bacteria activity, and functional diversity in urban riparian forests, highlighting the importance of considering soil microbes when managing urban ecosystems.